Clinical Evaluation for Sublingual Immunotherapy With Dermatophagoides farinae in Polysensitized Allergic Asthma Patients - Zhang, Ai-zhi; Liang, Mei-e; Chen, Xiao-xue; Wang, Yan-fen; Ma, Ke; Lin, Zhi; Xue, Kuan-kuan; Cao, Li-ru; Yang, Rong; Zhang, Huan-ping (Frontiers in Medicine, 2021)
Background: Many studies have demonstrated the efficacy of single allergen sublingual immunotherapy (SLIT) in polysensitized patients with allergic rhinitis (AR), but less is reported in polysensitized patients with allergic asthma (AS). Method: Data of one hundred and thirty-three adult patient with house dust mite (HDM)-induced AS who had been treated for 3 years was collected. These patients were divided into the control group (treated with low to moderate dose of inhaled glucocorticoids and long-acting β2 agonists, n=37) and the SLIT group (further treated with Dermatophagoides farinae drops, n=96). The SLIT group contained three subgroups: the single-allergen group (only sensitized to HDM, n=35), the 1-2 allergens group (HDM combined with 1-2 other allergens, n=32) and the 3 or more allergens group (HDM combined with 3 or more other allergens, n=29). The total asthma symptom score (TASS), total asthma medicine score (TAMS) and asthma control test (ACT) were assessed before treatment and at yearly visits. Forced expiratory volume in one second/forced vital capacity (FEV1/FVC) was assessed before treatment and at the end of SLIT. Results: TASS and ACT scores in the control group were significantly higher than that in the single-allergen group and the 1-2 allergens group after 1, 2 and 3 years of SLIT and significantly higher than that in the 3 or more allergens group after 3-year SLIT(all p＜0.05). TAMS of the control group was significantly higher than that of the other three groups after 0.5, 1, 2 and 3 years of SLIT(all p＜0.05). FEV1/FVC in the control group was significantly higher than baseline after 3 years of immunotherapy (p＜0.05). Conclusion: Patients sensitized to HDM with/without other allergens showed similar efficacy after 3 years of SLIT. However, the initial response of patients with 3 or more allergens was slower during immunotherapy process.